A climate database with varying drought-heat signatures for climate impact modelling - Tschumi, Elisabeth; Lienert, Sebastian; van der Wiel, Karin; Joos, Fortunat; Zscheischler, Jakob (Zenodo, 2020)
To allow for impact modelling for a wide range of sectors, we provide six scenarios with differing drought-heat signatures. Each scenario is 100 years long and we provide temperature variables (mean, minimum, maximum), precipitation, radiation (short- and longwave downward radiation and shortwave net radiation) and wind (zonal and meridional) at daily timescales. All variables are available at a regular 1◦×1◦grid over land, except Antarctica and large parts of Greenland. Leap days were removed, so there are 365×100 time steps for each scenario. E.T. and J.Z. acknowledge the Swiss National Science Foundation (Ambizione grant 179876). K.v.d.W. acknowledges funding for the HiWAVES3 project from the National Natural Science Foundation of China (41661144006)